Structural Simplification of Bedaquiline: the Discovery of 3‐(4‐(N, N‐Dimethylaminomethyl)phenyl)quinoline‐Derived Antitubercular Lead Compounds. (28th October 2016) - He, Chunxian; Preiss, Laura; Wang, Bin; Fu, Lei; Wen, Hui; Zhang, Xiang; Cui, Huaqing; Meier, Thomas; Yin, Dali
Abstract: Bedaquiline (BDQ) is a novel and highly potent last‐line antituberculosis drug that was approved by the US FDA in 2013. Owing to its stereo‐structural complexity, chemical synthesis and compound optimization are rather difficult and expensive. This study describes the structural simplification of bedaquiline while preserving antitubercular activity. The compound's structure was split into fragments and reassembled in various combinations while replacing the two chiral carbon atoms with an achiral linkage instead. Four series of analogues were designed; these candidates retained their potent antitubercular activity at sub‐microgram per mL concentrations against both sensitive and multidrug‐resistant (MDR) Mycobacterium tuberculosis strains. Six out of the top nine MIC‐ranked candidates were found to inhibit mycobacterial ATP synthesis activity with IC50 values between 20 and 40 μm, one had IC50 >66 μm, and two showed no inhibition, despite their antitubercular activity. These results provide a basis for the development of chemically less complex, lower‐cost bedaquiline derivatives and describe the identification of two derivatives with antitubercular activity against non‐ATP synthase related targets. Abstract : Anti‐TB streamlining : Synthesis of the new antituberculosis antibiotic bedaquiline is expensive and time consuming. To overcome difficulties met in the synthesis of bedaquiline, a fragment‐based strategy was used to create a new series of lead compounds with much simpler structures and no chiral centers. While these new lead compounds maintain their potent antitubercular activities toward Mycobacterium tuberculosis, they are less potent at inhibition of the molecular target of bedaquiline: the ATP synthase.